Outcome of moderate preterm and term babies at tertiary care centre - Balai, Shaitan Singh; Katara, Durgavati; Arora, Vivek (International Journal of Contemporary Pediatrics, 2018)
Background: To study the maternal risk factors, morbidity, mortality of moderate preterm in comparison to term neonates. Methods: This Cohort study involved two hundred fifty consecutively born moderate preterm and equal number of term newborns delivered in a tertiary care hospital. They were followed till discharge for morbidities and mortality. Detailed maternal and neonatal factors were studied and compared between the two groups. Results: Moderate preterm babies constituted 55% of all live preterm births during the study period. The odds of babies developing major morbidity was significantly more in those whose mothers had hypertension and infections (OR 2.69 95% CI: 1.55, 4.68 and 2.08, 95% CI: 1.6, 2.71 respectively). In the study group, 42.4% and 20.8% babies suffered major and minor morbidity compared to 8.4% and 6.8% of term controls respectively. moderate preterm neonates had significantly higher odds of developing morbidity like respiratory distress (12.4% vs. 5.6%, OR 2.21, 95%CI 1.21,4.11), need for non-invasive(17.3% vs. 5.7%, OR 3.05 95% CI 1.69, 5.47) and invasive ventilation (14.6% vs. 1.7%, OR 8.62, 95% CI 3.09, 24.04), sepsis (20.8% vs. 5.2%, OR 5.20, 95% CI 2.71, 9.99), seizures (22.8% vs. 4.8%, OR 4.75 95%CI 2.61, 8.63), shock (17.6% vs. 4.4%, OR 4.00 95% CI 2.12,7.56), and jaundice (26% vs. 6%, OR 4.33 95%CI 2.54, 7.39). By logistic regression, the odds of developing major morbidity decreased with increasing gestational age (aOR 0.28 95% CI 0.18, 0.45; p<0.001) and increased with hypertensive disease of pregnancy (aOR 2.16 95% CI 1.09, 4.260; p00.026). Conclusions: Moderate preterm neonates have significantly more mortality and morbidity compared to term controls. Maternal hypertension and lower gestational age are the strongest predictors of morbidity.